(untitled) (Research, Society and Development, 2020)
This work aims to characterize the profile of fishermen who make up the fisheries agreements in the municipalities of Araguacema and Couto Magalhães in Tocantins, and to provide subsidies for the development of public policies for the artisanal fishing sector in the region. We analyzed 90 questionnaires applied between the years 2015 and 2016, using descriptive statistics. There was the participation of mainly male fishermen, born in the state of Tocantins, mostly married or with stable unions, and with low schooling. The average age is 44±11. The high consumption of fish shows the importance of this resource in the food security of these communities, where 60% live exclusively from fishing. 46.7% has from 0 to 9 years of activity. The great majority has boat and engine (96.7% and 81.1%, respectively). Each fishery lasts up to more than 5 days, and for 34.4% it lasts up to 3 days. The fish is sold for 64.4% to the final consumer. The main fishing gear used are the line and hook, and the net, and the main species caught in the two municipalities are: the tucunaré (Cichla spp. ), surubim (Pseudoplatystoma punctifer), fidalgo (Ageneiosus ucayalensis), curvina (Plagioscion squamosissimus), and pacus (Metynnis sp.; Myleus sp.; Myloplus sp.; Mylossoma sp.).